Digital da’wah content creation training for university students - Rahim, Abdul; Maulana, Harry Fajar; Ridwan, Muhamad; Jumaydin, Jumaydin; Fayyaza, Adiela; Iye, Risman (Universitas Muhammadiyah Magelang, 2025)
The rapid development of digital technology has revolutionized the dissemination of Islamic da’wah (proselytizing), necessitating young generations, particularly university students, to become adaptive and creative agents of da’wah utilizing digital media. However, limitations in technical skills and low levels of digital literacy and communication ethics remain serious challenges. This community service activity aimed to enhance the capacity of students in producing digital da’wah content that is informative, engaging, and consistent with the principles of moderate Islamic da’wah. The training program was conducted over three days using a participatory approach, covering digital literacy, content production techniques, and Islamic communication ethics. Evaluation results showed a significant increase in participants’ understanding, rising from an average score of 58.3 in the pre-test to 84.1 in the post-test, with an N-Gain score of 61.8%. Furthermore, 87% of participants successfully produced da’wah content in video format, and 73% of them established dedicated social media accounts to disseminate their da’wah content. This training proved effective in transforming students’ roles from passive consumers into active creators of digital da’wah.